LEADING SECTOR AND ABSORPTION OF LABOR (Sektor Unggulan Dan Penyerapan Tenaga Kerja ) - Ismail A Ibrahim (Gorontalo Development Review, 2018)
Abstract Development must be viewed as a multidimensional process that includes a variety of fundamental changes to social structure, attitudes of the community, and national institutions, while continuing to pursue accelerated economic growth, handling income inequality, and alleviating poverty.The expected research objective is to analyze the leading sectors and employment in Gorontalo Regency so that the benefits of this study are expected: 1) as a reference in policy making related to the leading sector development strategy and Manpower Absorption in Gorontalo District, 2) can provide an overview of various potential existing sectors as an option to become workers so that they can provide their income every year in Gorontalo Regency, 3) can provide information and become an opportunity for investment investment which is the biggest part of available labor shelter in Gorontalo District.The Analysis Method used in this study is Location Quotient (LQ) to determine the role of the sector in the reference area (Gorontalo Province). And the results of the study indicate that the results of several economic sectors in Gorontalo Regency have economic (base) advantages: Sector mining and quarrying, Processing Industry Sector, Electricity and Gas Procurement Sector, Construction Sector, Information and Communication Sector, Financial Sector and Sector which have high employment absorption are Fisheries, Forestry and Agriculture, Processing Industry Sector. Abstrak Pembangunan harus dipandang sebagai suatu proses multidimensional yang mencakup berbagai perubahan mendasar atas struktur sosial, sikap-sikap masyarakat, dan institusi-institusi nasional, di samping tetap mengejar akselerasi pertumbuhan ekonomi, penanganan ketimpangan pendapatan, serta pengentasan kemisikinan.Adapun tujuan penelitian yang diharapkan adalah untuk menganalisis sektor unggulan dan penyerapan tenaga kerja di Kabupaten Gorontalo sehingga manfaat penelitian ini diharapkan : 1) sebagai acuan dalam pengambilan kebijakan terkait dengan strategi pengembangan sektor unggulan dan Penyerapan tenaga kerja di Kabupaten Gorontalo, 2) dapat memberikan gambaran dari berbagai potensi sektor unggulan yang ada sebagai pilihan untuk menjadi tenaga kerja sehingga dapat memberikan pendapatan mereka pada setiap tahunnya di Kabupaten Gorontalo, 3) dapat memberikan informasi dan menjadi peluang bagi penanaman isvestasi yang menjadi bagian yang terbesar bagi penampungan tenaga kerja yang tersedia di Kabupaten Gorontalo.Metode Analisis yang digunakan dalam penelitian ini adalah Location Quotient (LQ) untuk menentukan besarnya peranan sektor tersebut pada wilayah referensi (Provinsi Gorontalo).Dan hasil Penelitian menujukkan bahwa telah diperoleh hasil beberapa sektor ekonomi di Kabupaten Gorontalo mempunyai keunggulan ekonomi (basis) adalah :Sektor pertambangan dan penggalian, Sektor Industri Pengolahan, Sektor Pengadaan listrik dan gas, Sektor konstruksi, Sektor Informasi dan komunikasi, Sektor Keuangan dan Sektor yang memiliki kontribusi penyerapan tenaga kerja yang tinggi adalah Sektor Perikanan, Kehutanan dan pertanian, Sektor Sektor Industri Pengolahan.